2021
DOI: 10.1097/md.0000000000028334
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of ABO blood group to COVID-19 infections: clinico-hematological, radiological, and complications analysis

Abstract: In the wake of the COVID-19 pandemic, research indicates that the COVID-19 disease susceptibility varies among individuals depending on their ABO blood groups. Researchers globally commenced investigating potential methods to stratify cases according to prognosis depending on several clinical parameters. Since there is evidence of a link between ABO blood groups and disease susceptibility, it could be argued that there is a link between blood groups and disease manifestation and progression. The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…These findings are consistent with the study done by Jawdat et al in Saudi Arabia, which concluded that blood group phenotype B is a risk factor for COVID-19 disease, 16 On the contrary; Jiao Zhao et al found that blood group A was associated with an increased risk, whereas blood group O was associated with a decreased risk. 9 A similar study done in India in 2021 revealed that A, B, and RhD positive were found to be more susceptible to COVID-19 infection, whereas blood groups O, AB, and RhD negative were at a lower risk of COVID-19 infection, and no association was found between blood groups and susceptibility to the severity of disease and mortality in this study 25 In Table 4, we summarize other studies from Saudi Arabia that contained a control group (or used historic control data), 20,24,[26][27][28][29][30][31] focusing on blood group association with COVID-19 vulnerability and disease severity. We did not include two studies that lacked a proper control group or detailed statistical analysis.…”
Section: Discussionmentioning
confidence: 92%
“…These findings are consistent with the study done by Jawdat et al in Saudi Arabia, which concluded that blood group phenotype B is a risk factor for COVID-19 disease, 16 On the contrary; Jiao Zhao et al found that blood group A was associated with an increased risk, whereas blood group O was associated with a decreased risk. 9 A similar study done in India in 2021 revealed that A, B, and RhD positive were found to be more susceptible to COVID-19 infection, whereas blood groups O, AB, and RhD negative were at a lower risk of COVID-19 infection, and no association was found between blood groups and susceptibility to the severity of disease and mortality in this study 25 In Table 4, we summarize other studies from Saudi Arabia that contained a control group (or used historic control data), 20,24,[26][27][28][29][30][31] focusing on blood group association with COVID-19 vulnerability and disease severity. We did not include two studies that lacked a proper control group or detailed statistical analysis.…”
Section: Discussionmentioning
confidence: 92%
“…reported that symptoms were highly observed in blood group O, followed by A and B except for pharyngeal exudate in blood group A. 31 More recently, in a Spanish population-based prospective cohort study, Enguita-German et al. observed no association between ABO blood types and hospitalization, intensive care unit admission, or death in individuals with COVID-19.…”
Section: Discussionmentioning
confidence: 96%
“…30 In an observational clinico-hematological, radiological, and complication analysis of susceptibility to COVID-19 infection in Saudi Arabia, Kabrah et al reported that symptoms were highly observed in blood group O, followed by A and B except for pharyngeal exudate in blood group A. 31 More recently, in a Spanish population-based prospective cohort study, Enguita-German et al observed no association between ABO blood types and hospitalization, intensive care unit admission, or death in individuals with COVID-19. Regarding the risk of COVID-19 infection, they reported a protective effect in group O and a greater risk in A group.…”
Section: Discussionmentioning
confidence: 99%
“…( 29 ) Cohort / 8 330 ICU admission and mortality - Increased ICU admission in blood group AB KABRAH et al ., 2021, Saudi Arabia. ( 59 ) Cohort / 7 285 ICU admission and mortality - No significant difference HOILAND et al ., 2020, Canada. ( 44 ) Cross-sectional / 7 95 Mechanical ventilation - Increased need for mechanical ventilation in blood groups A and AB HALIM et al ., 2021, Blangadesh.…”
Section: Resultsmentioning
confidence: 99%
“…(2021) ( 26 ) Cohort ** * *** KABRAH et al . (2021) ( 59 ) Cohort *** * *** MATZHOLD et al . (2021) ( 27 ) Cohort *** * ** MULLINS et al .…”
Section: Methodsmentioning
confidence: 99%